Minoría lingüística: presión comunicativa y cultural hacia la persona sorda - Sanhueza Mendoza, Rodrigo; Morales Acosta, Gina Viviana (Pelícano, 2018)
Linguistic Minority: Communicative and Cultural Pressure towards the Deaf PersonResumenEl artículo aborda los conceptos de Minoría Lingüística, Opresión Comunicativa y Cultural, hacia la persona Sorda, como revisión teórica que permite abordar las relaciones comunicativas hegemónicas en la comunicación y las formas de considerar a un Otro diverso.La importancia para la comunidad (de Sordos) en la reivindicación como sujetos de derecho, que sus integrantes como punto de enunciación en una identidad Sorda.Abstract The article approaches the concepts of Linguistic Minority, Communicative and Cultural Oppression, towards the Deaf person, as a theoretical revision that allows to approach the hegemonic communicative relations in the communication and the ways to consider a different Other.The importance for the community (Deaf) in claiming as subjects of law, that its members as a point of enunciation in a Deaf identity.Key words: Linguistic Minority, Communicative Oppression, Deaf Culture, Deaf Subject, Sign Language.